Hedging of equity-linked contract with maximal success factor - Klusik, Przemysław (Zabezpieczenie kontraktu typu equity-linked z maksymalnym współczynnikiem sukcesu, 2021)
The author considers an equity-linked contract whose payoff depends on the lifetime of the policy holder and the stock price, and assumes the limited capital for hedging and provides the best strategy for an insurance company in the meaning of the so-called success factor 𝐸ℙ[𝟏{𝑉𝑇≥𝐷} + 𝟏{𝑉𝑇<𝐷} 𝑉𝑇 𝐷 ], where 𝑉𝑇 denotes the end value of the strategy and D is the payoff of the contract. The study is a generalisation of the work by Föllmer and Schied (2004), and Klusik and Palmowski (2011), but it considers the much more general ‘incompleteness’ of the market, among others, midterm nonmarket information signals and infinite nonmarket scenarios
Śląski Przegląd Statystyczny = Silesian Statistical Review, 2021, Nr 19 (25), s. 31-39
Keywords: quantile hedging; equity-linked contract; hedging kwantylowy; kontrakty equity-linked